IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) PADA MATERI SUHU DAN KALOR UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI SMA NEGERI 2 TONDANO - Lombo, Riris Liliana; Marianus; Rampengan, Alfrie Musa; Rende, Jeane Cornelda; Mahulae, Parno Sumanro (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2025)
The Two Stay Two Stray (TSTS) cooperative learning model is an approach that focuses on active interaction between students through discussion activities and information exchange between groups. This study was conducted with the aim of determining the effect of the TSTS model on the learning outcomes of students at Tondano 2Public High School on the subject of temperature and heat. The method applied in this study was a quasi-experiment with a non-equivalent pretest-posttest control group design,involving two classes, namely the experimental class and the controlclass. In the experimental class, the pretest results showed an average of 34 and increased to 83.05 in the posttest, while the control class experienced an increase from an average of 33.52 to 73.81. Furthermore, a statistical analysis in the form of an independent t-test was conducted, which yielded a sig. value of 0.0002 (<0.05), indicating that there was a significant difference in learning outcomes between the two groups. The application of the TSTS cooperative learning model proved to be effective in improving learning outcomes because it encouraged students to be more active, responsible, and directly participate in learning activities. From these results, it can be concluded that the application of the TSTS cooperative learning model has a positive effect on improving student learning outcomes on the topic of temperature and heat.